Comparative Analysis of Democratic Systems in Cambodia, Laos, and Thailand - Cai, Qinwen; Cai, Qinwen (Journal of Ecohumanism, 2024)
This paper analyses Cambodian, Laotian, and Thai democratic systems, emphasising specific political aspects and models of governance. Cambodia's budding democracy, shaped by its experience of dictatorial governance, is remarkably different from Lao's single-party communist regime. At a more complex level of democracy, Thailand, conversely, is a militarised civil administration huddled with stability in civil-military relations. Detailed analyses of political institutions, electoral systems, and civil liberties, among others, will reveal their strengths and weaknesses. The comprehensive literature review provides an understanding of how these regimes yield different outcomes regarding democracy, revealing some common challenges that bar their efforts to democratise and gain political stability. They indicate the huddles in achieving civil rights and freedoms for their populations. The study applies theories of democracy and authoritarian durability by examining political structures, voting procedures, and citizen freedoms. Other aspects explored in this paper include the effect of these political settings on regional peace and stability, including a more extensive view of Southeast Asian development. In addition, the factors that contribute to democratic governance, such as media freedom, are explored. The comparative analysis further focuses on the implications of efforts towards democracy in the region.